Post-buckling analysis of elastoplastic sandwich columns by means of an enriched 1D finite element model. (15th December 2017) - Sad Saoud, Kahina; Le Grognec, Philippe
Abstract: An advantageous 1D finite element model is designed in the present paper so as to analyze in an efficient way the post-buckling behavior of sandwich beams, known to be commonly responsible for the final collapse of such structures. An enriched beam formulation is defined, where the relatively thin skin layers are modeled as Timoshenko–Reissner beams, as they may undergo large rotations at advanced post-buckled stages. As for the homogeneous core layer, its complex behavior is represented by specific kinematics involving hyperbolic functions. The numerical model is developed within a total Lagrangian formulation framework, considering purely elastic behavior for the skins and an elastoplastic core material. The 1D finite element program incorporates effective incremental control techniques, namely arc-length methods and branch-switching procedures, in order to cope with limit and bifurcation points due to material and geometric non-linearities. A series of incremental calculations is performed in the case of axially compressed columns, exhibiting both global and local buckling modes depending on the geometric and material features. Secondary bifurcations, giving rise to unstable post-buckled solutions, are encountered in most cases due to the operating modal interaction phenomena. The results are compared with reference numerical computations achieved using a 2D finite element customized program.